(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main purpose of this research was Mental Health and Academic Achievement among Urban and Rural Secondary School Students. The total sample consisted of 80 students (Urban and Rural) were taken. The research tool for mental health was measured by D. J. Bhatt and Gita R. Gida (1992). While the tool for Academic Achievement was measured by T. R. Sharma (2002). Here t-test was applied to check the significance of the difference between mental health and academic achievement in urban and rural secondary school students. To check the relationship between mental health and academic achievement correlation mental was used. Results revealed that significant difference in mental health and academic achievement with respect to both urban and rural secondary school students. While to correlation between mental health and academic achievement reveals a high positive correlation between urban and rural secondary school students.